Relativistic aberration of light as a corollary of relativity of simultaneity - GJurchinovski, Aleksandar (IOP Publishing, 2004)
A new derivation of the relativistic aberration formula for a plane-polarized light wave is presented that does not require any use of the Lorentz transformation. The method is based on a modification of the Huygens-Fresnel principle to include the relativistic effects introduced by the relative motion between the observer and the emitter. The derivation clearly shows that the aberration formula is a direct consequence of the relative simultaneity.
Keywords: Physics - Optics; Physics - Optics; Astrophysics; Physics - Classical Physics